(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Social media has gained significant prominence in the current era. Organizations are consistently seeking methods to incorporate this emerging platform into their marketing strategies in order to stimulate expansion. The findings of a study regarding the social media experiences of marketers and consumers in the state of Delhi are presented in the article. A survey of consumers and marketers was conducted as part of the quantitative research methodology for this study. Information regarding the beliefs, policies, goals, and experiences of marketers regarding social media marketing, as well as the causes, experiences, and beliefs of consumers regarding their social media presence, was gathered via a self-designed questionnaire. According to the findings, consumers exhibited a distinct inclination towards the influence of social media on their purchasing decisions and varied patterns of engagement, whereas marketers predominantly employed social platforms as a means to disseminate information and gain customer insights. There is considerable consensus about the efficacy and cost-efficiency of social media marketing, despite challenges in handling negative feedback and calculating returns. This research highlights the significance of utilizing these observations to develop sophisticated tactics for marketers, thereby improving their efficiency in navigating the ever-changing field of social media marketing